The Counsellor as Teacher in Career Development - Lucas, Dennis (Canadian Journal of Counselling and Psychotherapy, 2012)
School counsellors are moving away from models based on psychotherapy to teaching models based on the development of normal individuals in educational settings. They are engaging more and more in activities which may be described as instructional. The area of career development provides an illustration of the types ofskills and values which counsellors "teach".